Microsurgery for groin lymphocele and lymphedema after oncologic surgery. Issue 1 (11th July 2013) - Boccardo, Francesco; Dessalvi, Sara; Campisi, Corrado; Molinari, Lidia; Spinaci, Stefano; Talamo, Giuseppina; Campisi, Corradino
Abstract : Groin lymphocele (GL) is a frequent complication of inguinal lymph node dissection, and conservative treatment is not always successful. Different surgical methods have been used to treat lymphoceles arising from lymphatics injured during groin surgery. However, they all involve the closure of lymphatics merging at the lymphocele, increasing the risk of postoperative lower limb lymphedema or of worsening lymphedema if already clinically evident. We assessed the efficacy of a diagnostic and therapeutic protocol to manage inguinal lymphoceles using lymphoscintigraphy (LS) and microsurgical procedures. Sixteen GL [seven associated with leg lymphedema (LL)] were studied by LS preoperatively and treated by complete excision of lymphocele and microsurgical lymphatic‐venous anastomoses between afferent lymphatics and a collateral branch of great saphenous vein. Lower limb lymphatics were identified intraoperatively using Patent Blue dye injection. Nine patients without lymphedema had complete healing of lymphocele and no appearance of lower limb postoperative lymphedema. The other seven patients with associated secondary lymphedema had complete disappearance of lymphocele and a remarkable reduction of leg volume. Four of them completely recovered without the need of any compression garment, after the first year postoperative. Inguinal lymphocele nonresponsive to conservative treatment can be advantageously studied by LS and successfully treated by microsurgical reconstructive procedures, above all if associated to LL. © 2013 Wiley Periodicals, Inc. Microsurgery 34:10–13, 2014.